Minimal prospects for radio detection of extensive air showers in the atmosphere of Jupiter - Bray, J. D.; Nelles, Anna (Astrophysical Journal, 2016)
One possible approach for detecting ultra-high-energy cosmic rays and neutrinos is to search for radio emission from extensive air showers created when they interact in the atmosphere of Jupiter, effectively utilizing Jupiter as a particle detector. We investigate the potential of this approach. For searches with current or planned radio telescopes we find that the effective area for detection of cosmic rays is substantial (∼3 × 107 km2), but the acceptance angle is so small that the typical geometric aperture (∼103 km2 sr) is less than that of existing terrestrial detectors, and cosmic rays also cannot be detected below an extremely high threshold energy (∼1023 eV). The geometric aperture for neutrinos is slightly larger, and greater sensitivity can be achieved with a radio detector on a Jupiter-orbiting satellite, but in neither case is this sufficient to constitute a practical detection technique. Exploitation of the large surface area of Jupiter for detecting ultra-high-energy particles remains a long-term prospect that will require a different technique, such as orbital fluorescence detection.
CRIS-Team Scopus Importer:2023-08-15
Keywords: astroparticle physics; cosmic rays; neutrinos; planets and satellites: individual (Jupiter)